The day after tomorrow - Emmerich, Roland; Gordon, Mark, 1956-; Nachmanoff, Jeffrey; Quaid, Dennis; Gyllenhaal, Jake, 1980-; Rossum, Emmy, 1986-; Mihok, Dash, 1974-; Sanders, Jay O., 1953-; Ward, Sela.; Nichols, Austin, 1980-; Smith, Arjay, 1983-; Tomita, Tamlyn; et al. ([United States] : 20th Century Fox Home Entertainment, 2004)
When global warming triggers the onset of a new Ice Age, tornadoes flatten Los Angeles, a tidal wave engulfs New York City and the entire Northern Hemisphere begns to freeze solid. Now, climatologist Jack Hall, his son Sam, and a small band of survivors must ride out the growing superstorm and stay alive in the face of an enemy more powerful and relentless than anything anyone has ever encountered: Mother Nature.
Special features: commentary by director Roland Emmerich and producer Mark Gordon; commentary by writer Jeffrey Nachmanoff, cinematographer Ueli Steiger, editor David Brenner, and production designer Barry Chusid; deleted scenes; interactive audio demo; DVD-ROM link to hour-long exclusive material.
Director of photography, Ueli Steiger ; editor, David Brenner ; music, Harald Kloser ; costume designer, Reně April ; production designer, Barry Chusid ; visual effects supervisors, Greg Anderson ... [et al.].
Dennis Quaid, Jake Gyllenhaal, Emmy Rossum, Dash Mihok, Jay O. Sanders, Sela Ward, Austin Nichols, Arjay Smith, Tamlyn Tomita.
MPAA rating: PG-13; for intense situations of peril.
DVD.
In English with Spanish subtitles; closed-captioned.
Keywords: Global warming -- Drama; Climatologists -- Drama; Glacial epoch -- Drama; Films for the hearing impaired